12th NCERT Continuity and Differentiability Miscellaneous 5 Questions 23
Do or do not
There is no try
Differentiate w.r.t x the function in Exercise 1 to 11

Question (1)

(3x2 - 9x + 5 )9

Solution

Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = 9{\left( {3{x^2} - 9x + 5} \right)^8}\frac{d}{{dx}}\left( {3{x^2} - 9x + 5} \right)$ $\frac{{dy}}{{dx}} = 9{\left( {3{x^2} - 9x + 5} \right)^8}\left( {6x - 9} \right)$ $\frac{{dy}}{{dx}} = 9{\left( {3{x^2} - 9x + 5} \right)^8}3\left( {2x - 3} \right)$ $\frac{{dy}}{{dx}} = 27\left( {2x - 3} \right){\left( {3{x^2} - 9x + 5} \right)^8}$

Question (2)

sin3 + cos6x

Solution

Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = 3{\sin ^2}x\cos x + 6{\cos ^5}x \cdot \left( { - \sin x} \right)$ $\frac{{dy}}{{dx}} = 3{\sin ^2}x\cos x - 6\sin x{\cos ^5}x$ $\frac{{dy}}{{dx}} = 3\sin x\cos x\left( {\sin x - 2{{\cos }^4}x} \right)$

Question (3)

(5x)3cos2x

Solution

Take log on both side log y = log[(5x)3cos2x]
log y = 3cos2x log(5x)
Differentiating w.r.t. x, $\frac{1}{y}\frac{{dy}}{{dx}} = 3\left[ {\cos 2x\frac{d}{{dx}}\log 5x + \log 5x\frac{d}{{dx}}\cos 2x} \right]$ $\frac{{dy}}{{dx}} = 3y\left[ {\frac{{\cos 2x}}{{\require{cancel} \cancel{5}x}} \times \cancel{5} + \log 5x \cdot \left( { - \sin 2x} \right)2} \right]$ $\frac{{dy}}{{dx}} = 3{\left( {5x} \right)^{3\cos 2x}}\left[ {\frac{{\cos 2x}}{x} - 2\sin 2x\log 5x} \right]$

Question (4)

sin-1(x√x). 0 ≤ x ≤ 1

Solution

y = sin-1(x3/2)
Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = \frac{1}{{\sqrt {1 - {{\left( {{x^{\frac{3}{2}}}} \right)}^2}} }}\frac{d}{{dx}}{x^{\frac{3}{2}}}$ $\frac{{dy}}{{dx}} = \frac{1}{{\sqrt {1 - {x^3}} }}\frac{3}{2}{x^{\frac{1}{2}}}$ $\frac{{dy}}{{dx}} = \frac{3}{2}\frac{{\sqrt x }}{{\sqrt {1 - {x^3}} }}$ $\frac{{dy}}{{dx}} = \frac{3}{2}\sqrt {\frac{x}{{1 - {x^3}}}}$

Question (5)

$\frac{{{{\cos }^{ - 1}}\frac{x}{2}}}{{\sqrt {2x + 7} }}$ -2 < x < 2

Solution

Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = \frac{{\sqrt {2x + 7} \frac{d}{{dx}}{{\cos }^{ - 1}}\frac{x}{2} - {{\cos }^{ - 1}}\frac{x}{2}\frac{d}{{dx}}\sqrt {2x + 7} }}{{{{\left( {\sqrt {2x + 7} } \right)}^2}}}$ $\frac{{dy}}{{dx}} = \frac{1}{{2x + 7}}\left[ {\sqrt {2x + 7} \times \frac{{ - 1}}{{\sqrt {1 - {{\left( {\frac{x}{2}} \right)}^2}} }} \times \frac{1}{2} - {{\cos }^{ - 1}}\left( {\frac{x}{2}} \right)\frac{1}{{\cancel{2}\sqrt {2x + 7} }} \times\cancel{2}} \right]$ $\frac{{dy}}{{dx}} = \frac{1}{{2x + 7}}\left[ {\frac{{ - \sqrt {2x + 7} }}{{\cancel{2}\frac{{\sqrt {4 - {x^2}} }}{\cancel{2}}}} - \frac{{{{\cos }^{ - 1}}\left( {\frac{x}{2}} \right)}}{{\sqrt {2x + 7} }}} \right]$ $\frac{{dy}}{{dx}} = \frac{{ - \sqrt {2x + 7} }}{{\left( {2x + 7} \right)\sqrt {4 - {x^2}} }} - \frac{{{{\cos }^{ - 1}}\frac{x}{2}}}{{{{\left( {2x + 7} \right)}^{\frac{3}{2}}}}}$ $\frac{{dy}}{{dx}} = \frac{{ - 1}}{{\sqrt {2x + 7} \sqrt {4 - {x^2}} }} - \frac{{{{\cos }^{ - 1}}\frac{x}{2}}}{{{{\left( {2x + 7} \right)}^{\frac{3}{2}}}}}$

Question (6)

${\cot ^{ - 1}}\left[ {\frac{{\sqrt {1 + \sin x} + \sqrt {1 - \sin x} }}{{\sqrt {1 + \sin x} - \sqrt {1 - \sin x} }}} \right]$ 0 < x < (π/2)

Solution

$y = {\cot ^{ - 1}}\left[ {\frac{{\sqrt {1 + \sin x} + \sqrt {1 - \sin x} }}{{\sqrt {1 + \sin x} - \sqrt {1 - \sin x} }}} \right]$ $y = {\cot ^{ - 1}}\left[ {\frac{{\sqrt {1 + \sin x} + \sqrt {1 - \sin x} }}{{\sqrt {1 + \sin x} - \sqrt {1 - \sin x} }} \times \frac{{\sqrt {1 + \sin x} + \sqrt {1 - \sin x} }}{{\sqrt {1 + \sin x} + \sqrt {1 - \sin x} }}} \right]$ $y = {\cot ^{ - 1}}\left[ {\frac{{1 + \sin x + 1 - \sin x + 2\sqrt {1 - {{\sin }^2}x} }}{{\left( {1 + \sin x} \right) - \left( {1 - \sin x} \right)}}} \right]$ $y = {\cot ^{ - 1}}\left[ {\frac{{2 + 2\cos x}}{{2\sin x}}} \right]$ $y = {\cot ^{ - 1}}\left[ {\frac{{\cancel{2}\left( {1 + \cos x} \right)}}{{\cancel{2}\sin x}}} \right]$ $y = {\cot ^{ - 1}}\left[ {\frac{{\cancel{2}{{\cos }^2}\frac{x}{2}}}{{\cancel{2}\sin \frac{x}{2}\cos \frac{x}{2}}}} \right]$ $y = {\cot ^{ - 1}}\left( {\cot \frac{x}{2}} \right)$ $y = \frac{x}{2}$ Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = \frac{1}{2}$

Question (7)

(logx)logx, x > 1

Solution

Take log on both sides
logy = log[(logx)logx]
log y = logx [log (logx) ]
Differentiating w.r.t. x, $\frac{1}{y}\frac{{dy}}{{dx}} = \log x\frac{d}{{dx}}\log \left( {\log x} \right) + \log \left( {\log x} \right)\frac{d}{{dx}}\log x$ $\frac{1}{y}\frac{{dy}}{{dx}} = \log x\frac{1}{{\log x}}\frac{1}{x} + \log \left( {\log x} \right)\frac{1}{x}$ $\frac{{dy}}{{dx}} = y\left[ {\frac{1}{x} + \frac{{\log \left( {\log x} \right)}}{x}} \right]$ $\frac{{dy}}{{dx}} = {\left( {\log x} \right)^{\log x}}\left[ {\frac{1}{x} + \frac{{\log \left( {\log x} \right)}}{x}} \right]$

Question (8)

cos(a cos x + b sin x), for some constant a and b

Solution

y = cos(a cos x + b sin x)
Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = - \sin \left( {a\cos x + b\sin x} \right) \cdot \frac{d}{{dx}}\left( {a\cos x + b\sin x} \right)$ $\frac{{dy}}{{dx}} = - \sin \left( {a\cos x + b\sin x} \right) \cdot \left[ {a\left( { - \sin x} \right) + b\cos x} \right]$ $\frac{{dy}}{{dx}} = - \sin \left( {a\cos x + b\sin x} \right)\left( { - a\sin x + b\cos x} \right)$ $\frac{{dy}}{{dx}} = \left( {a\sin x - b\cos x} \right)\sin \left( {a\cos x + b\sin x} \right)$

Question (9)

( sin x - cos x)(sinx - cosx), π/4 < x < 3π/4

Solution

y = ( sin x - cos x)(sinx - cosx)
Take log on both side
log y = (sinx-cosx) log(sinx-cosx)
Differentiating w.r.t. x, $\frac{1}{y}\frac{{dy}}{{dx}} = \left( {\sin x - \cos x} \right)\frac{d}{{dx}}\log \left( {\sin x - \cos x} \right) + \log \left( {\sin x - \cos x} \right)\frac{d}{{dx}}\left( {\sin x - \cos x} \right)$ $\frac{1}{y}\frac{{dy}}{{dx}} = \frac{{\left( {\sin x - \cos x} \right)}}{{\left( {\sin x - \cos x} \right)}}\frac{d}{{dx}}\left( {\sin x - \cos x} \right) + \log \left( {\sin x - \cos x} \right)\left( {\cos x - \left( { - \sin x} \right)} \right)$ $\frac{1}{y}\frac{{dy}}{{dx}} = \left[ {\cos x - \left( { - \sin x} \right)} \right] + \log \left( {\sin x - \cos x} \right)\left( {\cos x + \sin x} \right)$ $\frac{{dy}}{{dx}} = y\left[ {\cos x + \sin x} \right]\left[ {1 + \log \left( {\sin x - \cos x} \right)} \right]$ $\frac{{dy}}{{dx}} = {\left( {\sin x - \cos x} \right)^{\sin x - \cos x}}\left( {\cos x + \sin x} \right)\left[ {1 + \log \left( {\sin x - \cos x} \right)} \right]$

Question (10)

xx + xa + ax+ aa, for some fixed a> 0 and x> 0

Solution

y = xx + xa + ax+ aa
Here xx is variable raised to variable to find its derivative. We have to take log
For xa . ax jave formula and aa = constant
Let u = xx Take log on both side
log u = xlogx
Differentiating w.r.t. x, $\frac{1}{u}\frac{{du}}{{dx}} = x\frac{d}{{dx}}\log x + \log x\frac{d}{{dx}}x$ $\frac{1}{u}\frac{{du}}{{dx}} = x\frac{1}{x} + \log x$ $\frac{{du}}{{dx}} = u\left[ {1 + \log x} \right]$ $\frac{{du}}{{dx}} = {x^x}\left( {1 + \log x} \right)$ Now y = xx + xa + ax+ aa

y = u+xa+ax+aa
Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = \frac{{du}}{{dx}} + a{x^{a - 1}} + {a^x}\log a + 0$ $\frac{{dy}}{{dx}} = {x^x}\left( {1 + \log x} \right) + a{x^{a - 1}} + {a^x}\log a$

Question (11)

xx2-3 + (x-3)x2 , for x > 3

Solution

Let u = xx2-3
Take log on both side
log u = (x2-3)log x
Differentiating w.r.t. x,
$\frac{1}{u}\frac{{du}}{{dx}} = \left( {{x^2} - 3} \right)\frac{d}{{dx}}\log x + \log x\frac{d}{{dx}}\left( {{x^2} - 3} \right)$ $\frac{1}{u}\frac{{du}}{{dx}} = \left( {{x^2} - 3} \right)\frac{1}{x} + \log x\left( {2x} \right)$ $\frac{{du}}{{dx}} = u\left[ {x - \frac{3}{x} + 2x\log x} \right]$ $\frac{{du}}{{dx}} = {x^{{x^2} - 3}}\left[ {x - \frac{3}{x} + 2x\log x} \right]$ Let v= (x-3)x2
Take log on both side
log v = x2 log(x-3)
Differentiating w.r.t. x,
$\frac{1}{v}\frac{{dv}}{{dx}} = {x^2}\frac{d}{{dx}}\log \left( {x - 3} \right) + \log \left( {x - 3} \right)\frac{d}{{dx}}{x^2}$ $\frac{1}{v}\frac{{dv}}{{dx}} = \frac{{{x^2}}}{{x - 3}} + 2x\log \left( {x - 3} \right)$ $\frac{{dv}}{{dx}} = v\left[ {\frac{{{x^2}}}{{x - 3}} + 2x\log \left( {x - 3} \right)} \right]$ $\frac{{dv}}{{dx}} = {\left( {x - 3} \right)^{{x^2}}}\left[ {\frac{{{x^2}}}{{x - 3}} + 2x\log \left( {x - 3} \right)} \right]$ Now y = (x)x2-3 + (x-3)x2
y = u + v
Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = \frac{{du}}{{dx}} + \frac{{dv}}{{dx}}$ $\frac{{dy}}{{dx}} = {x^{{x^2} - 3}}\left[ {\frac{{{x^2} - 3}}{x} + 2x\log x} \right] + {\left( x \right)^{{x^2} - 3}}\left[ {\frac{{{x^2}}}{{x - 3}} + 2x\log \left( {x - 3} \right)} \right]$

Question (12)

Find dy/dx. if y =12 ( 1 - cost),
x = 10(t - sin t) , π/2 < t < π/2

Solution

Differentiating w.r.t. t, $\frac{{dy}}{{dt}} = 12\left( {0 - \left( { - \sin t} \right)} \right)$ $\frac{{dy}}{{dt}} = 12\sin t$ x = 10 (t - sint)
Differentiating w.r.t. t, $\frac{{dx}}{{dt}} = 10\left( {1 - \cos t} \right)$ $\text{Now} \quad \frac{{dy}}{{dx}} = \frac{{\frac{{dy}}{{dt}}}}{{\frac{{dx}}{{dt}}}} = \frac{{12\sin t}}{{10\left( {1 - \cos t} \right)}}$ $\frac{{dy}}{{dx}} = \frac{{\cancel{12}^6\left( {\cancel{2}\sin \frac{t}{2}\cos \frac{t}{2}} \right)}}{{\cancel{10}_5\left( {\cancel{2}{{\sin }^2}\frac{t}{2}} \right)}}$ $\frac{{dy}}{{dx}} = \frac{6}{5}\frac{{\cos \frac{t}{2}}}{{\sin \frac{t}{2}}}$ $\frac{{dy}}{{dx}} = \frac{6}{5}\cot \left( {\frac{t}{2}} \right)$

Question (13)

Find dy/dx. if y = sin-1x + sin-1 √(1-x2), -1≤ x ≤ 1

Solution

$y = {\sin ^{ - 1}}x + {\sin ^{ - 1}}\sqrt {1 - {x^2}}$ Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = \frac{1}{{\sqrt {1 - {x^2}} }} + \frac{1}{{\sqrt {1 - {{\left( {\sqrt {1 - {x^2}} } \right)}^2}} }}\frac{d}{{dx}}\sqrt {1 - {x^2}}$ $\frac{{dy}}{{dx}} = \frac{1}{{\sqrt {1 - {x^2}} }} + \frac{1}{{\sqrt {1 - 1 + {x^2}} }}\frac{1}{{2\sqrt {1 - {x^2}} }}\left( { - 2x} \right)$ $\frac{{dy}}{{dx}} = \frac{1}{{\sqrt {1 - {x^2}} }} + \frac{1}{x}\frac{{ - x}}{{\sqrt {1 - {x^2}} }}$ $\frac{{dy}}{{dx}} = \frac{1}{{\sqrt {1 - {x^2}} }} - \frac{1}{{\sqrt {1 - {x^2}} }} = 0$

Question (14)

$x\sqrt {1 + y} + y\sqrt {1 + x} = 0$ for -1 < x < 1, prove that $\frac{{dy}}{{dx}} = - \frac{1}{{{{\left( {1 + x} \right)}^2}}}$

Solution

$x\sqrt {1 + y} = - y\sqrt {1 + x}$ Squaring on both side
x2 ( 1 + y) = y2 ( 1 + x)
x2 + x2y = y2 + xy2
x2y - xy2+x2-y2 = 0
xy(x-y) + (x-y)(x+y) = 0
(x-y)(xy+x+y) = 0
x - y = 0  OR  xy+x+y = 0
y = x  OR  xy + y= -x
y=x  OR  y = -x/1+x
but if y = x it will not satisfy the equation $\therefore y = \frac{{ - x}}{{1 + x}}$ Differentiating w.r.t. x, $\frac{{dy}}{{dx}} = - \left[ {\frac{{\left( {1 + x} \right)\frac{d}{{dx}}x - x\frac{d}{{dx}}\left( {1 + x} \right)}}{{{{\left( {1 + x} \right)}^2}}}} \right]$ $\frac{{dy}}{{dx}} = - \left[ {\frac{{\left( {1 + x} \right)1 - x}}{{{{\left( {1 + x} \right)}^2}}}} \right]$ $\frac{{dy}}{{dx}} = - \left[ {\frac{{1 + x - x}}{{{{\left( {1 + x} \right)}^2}}}} \right]$ $\frac{{dy}}{{dx}} = - \frac{1}{{{{\left( {1 + x} \right)}^2}}}$

Question (15)

If (x-a)2 + (y-b)2 = c2, for some c > 0, prove that $\frac{{{{\left[ {1 + {{\left( {\frac{{dy}}{{dx}}} \right)}^2}} \right]}^{\frac{3}{2}}}}}{{\frac{{{d^2}y}}{{d{x^2}}}}}$ is a constant independant of a and b

Solution

Differentiating w.r.t. x, $2\left( {x - a} \right) + 2\left( {y - b} \right)\frac{{dy}}{{dx}} = 0$ $2\left( {y - b} \right)\frac{{dy}}{{dx}} = - 2\left( {x - a} \right)$ $\frac{{dy}}{{dx}} = \frac{{ - \left( {x - a} \right)}}{{\left( {y - b} \right)}}$ Differentiating w.r.t. x, again $\frac{{{d^2}y}}{{d{x^2}}} = - \left[ {\frac{{\left( {y - b} \right)\frac{d}{{dx}}\left( {x - a} \right) - \left( {x - a} \right)\frac{d}{{dx}}\left( {y - b} \right)}}{{{{\left( {y - b} \right)}^2}}}} \right]$ $\frac{{{d^2}y}}{{d{x^2}}} = \frac{{ - 1}}{{{{\left( {y - b} \right)}^2}}}\left[ {\left( {y - b} \right) - \left( {x - a} \right)\frac{d}{{dx}}y} \right]$ $\frac{{{d^2}y}}{{d{x^2}}} = \frac{{ - 1}}{{{{\left( {y - b} \right)}^2}}}\left[ {\left( {y - b} \right) - \left( {x - a} \right)\left( {\frac{{ - \left( {x - a} \right)}}{{y - b}}} \right)} \right]$ $\frac{{{d^2}y}}{{d{x^2}}} = \frac{{ - 1}}{{{{\left( {y - b} \right)}^2}}}\left[ {\left( {y - b} \right) + \frac{{{{\left( {x - a} \right)}^2}}}{{y - b}}} \right]$ $\frac{{{d^2}y}}{{d{x^2}}} = \frac{{ - 1}}{{{{\left( {y - b} \right)}^2}}}\left[ {\frac{{{{\left( {y - b} \right)}^2} + {{\left( {x - a} \right)}^2}}}{{y - b}}} \right]$ $\frac{{{d^2}y}}{{d{x^2}}} = \frac{{ - {c^2}}}{{{{\left( {y - b} \right)}^3}}}$ $LHS = \frac{{{{\left[ {1 + {{\left( {\frac{{dy}}{{dx}}} \right)}^2}} \right]}^{\frac{3}{2}}}}}{{\frac{{{d^2}y}}{{d{x^2}}}}}$ $LHS = \frac{{{{\left[ {1 + {{\left( {\frac{{ - \left( {x - a} \right)}}{{y - b}}} \right)}^2}} \right]}^{\frac{3}{2}}}}}{{\frac{{ - {c^2}}}{{{{\left( {y - b} \right)}^3}}}}}$ $LHS = \frac{{{{\left( {y - b} \right)}^3}}}{{-{c^2}}} \times {\left[ {1 + \frac{{{{\left( {x - a} \right)}^2}}}{{{{\left( {y - b} \right)}^2}}}} \right]^{\frac{3}{2}}}$ $LHS = \frac{{{{\left( {y - b} \right)}^3}}}{{-{c^2}}} \times {\left[ {\frac{{{{\left( {y - b} \right)}^2} + {{\left( {x - a} \right)}^2}}}{{{{\left( {y - b} \right)}^2}}}} \right]^{\frac{3}{2}}}$ $LHS = \frac{{{{\left( {y - b} \right)}^3}}}{{ - {c^2}}} \times {\left( {\frac{{{c^2}}}{{{{\left( {y - b} \right)}^2}}}} \right)^{\frac{3}{2}}}$ $LHS = \frac{{{{\left( {y - b} \right)}^3}}}{{ - {c^2}}} \times \frac{{{c^3}}}{{{{\left( {y - b} \right)}^3}}}$ $LHS = - c$ LHS = constant

Question (16)

If cos y = x cos (a+y), with cos a ≠ ±1 prove that $\frac{{dy}}{{dx}} = \frac{{{{\cos }^2}\left( {a + y} \right)}}{{\sin a}}$

Solution

$\therefore x = \frac{{\cos y}}{{\cos \left( {a + y} \right)}}$ Differentiating w.r.t. y, $\frac{{dx}}{{dy}} = \frac{{\cos \left( {a + y} \right)\frac{d}{{dy}}\cos y - \cos y\frac{d}{{dy}}\cos \left( {a + y} \right)}}{{{{\cos }^2}\left( {a + y} \right)}}$ $\frac{{dx}}{{dy}} = \frac{{\cos \left( {a + y} \right)\left( { - \sin y} \right) - \cos y\left( { - \sin \left( {a + y} \right)} \right)}}{{{{\cos }^2}\left( {a + y} \right)}}$ $\frac{{dx}}{{dy}} = \frac{{ - \cos \left( {a + y} \right)\sin y + \sin \left( {a + y} \right)\cos y}}{{{{\cos }^2}\left( {a + y} \right)}}$ $\frac{{dx}}{{dy}} = \frac{{\sin \left( {a + y} \right)\cos y - \cos \left( {a + y} \right)\sin y}}{{{{\cos }^2}\left( {a + y} \right)}}$ $\frac{{dy}}{{dx}} = \frac{{\sin \left( {a + y - y} \right)}}{{{{\cos }^2}\left( {a + y} \right)}}$ $\frac{{dx}}{{dy}} = \frac{{\sin a}}{{{{\cos }^2}\left( {a + y} \right)}}$ $\frac{{dy}}{{dx}} = \frac{1}{{\frac{{dx}}{{dy}}}}$ $\frac{{dy}}{{dx}} = \frac{{{{\cos }^2}\left( {a + y} \right)}}{{\sin a}}$

Question (17)

If x = a(cost + t sint) and y= a(sint - tcost) find $\frac{{{d^2}y}}{{d{x^2}}}$

Solution

Differentiating w.r.t. t $\frac{{dx}}{{dt}} = a\left[ { - \sin t + \left( {t\frac{d}{{dt}}\sin t + \sin t\frac{d}{{dt}}t} \right)} \right]$ $\frac{{dx}}{{dt}} = a\left[ { - \sin t + t\cos t + \sin t} \right]$ $\frac{{dx}}{{dt}} = at\cos t$ Differentiating w.r.t. t $\frac{{dy}}{{dt}} = a\left[ {\cos t - \left( {t\frac{d}{{dt}}\cos t + \cos t\frac{d}{{dt}}t} \right)} \right]$ $\frac{{dy}}{{dt}} = a\left[ {\cos t - t\left( { - \sin t} \right) - \cos t} \right]$ $\frac{{dy}}{{dt}} = at\sin t$ $\frac{{dy}}{{dx}} = \frac{{\frac{{dy}}{{dt}}}}{{\frac{{dx}}{{dt}}}}$ $\frac{{dy}}{{dx}} = \frac{{at\sin t}}{{at\cos t}}$ $\frac{{dy}}{{dx}} = \tan t$ Differentiating w.r.t. x $\frac{{{d^2}y}}{{d{x^2}}} = \frac{d}{{dx}}\tan t$ $\frac{{{d^2}y}}{{d{x^2}}} = {\sec ^2}t\frac{{dt}}{{dx}}$ $\frac{{{d^2}y}}{{d{x^2}}} = {\sec ^2}t\frac{1}{{at\cos t}}$ $\frac{{{d^2}y}}{{d{x^2}}} = \frac{{{{\sec }^3}t}}{{at}}$

Question (18)

If f(x) = |x|3, show that f"(x) exists for all real x and find it

Solution

|x| = x ; x ≥ 0
|x| = -x ; x <0
Let f(x) = x3
If x ≥ 0
f(x) = x3
f'(x) = 3x2
f"(x) = 6x
If x< 0
f(x) = - x3
f'(x) = -3x2
f"(x) = -6x
f"(x) exists for all real number x
f"(x) = 6x , x ≥ 0
f"(x) = -6x, x< 0

Question (19)

Using mathematical induction prove that $\frac{d}{{dx}}{x^n} = n{x^{n - 1}}$ for all positive inegers n

Solution

Let us prove for n = 1
$\text{LHS} =\qquad \frac{d}{{dx}}x = 1$ RHS= 1x1-1 = 1 = LHS
It is true for n=1
Let us assume it is true for n = k $\therefore \frac{d}{{dx}}{x^k} = k{x^{k - 1}}$ Let us prove for n = k+1
that is prove $\frac{d}{{dx}}{x^{k + 1}} = \left( {k + 1} \right){x^k}$ Now $\frac{d}{{dx}}{x^{k + 1}} = \frac{d}{{dx}}\left( {x \cdot {x^k}} \right)$ by product rule $\frac{d}{{dx}}{x^{k + 1}} = x\frac{d}{{dx}}{x^k} + {x^k}\frac{d}{{dx}}x$ $\frac{d}{{dx}}{x^{k + 1}} = x \cdot k{x^{k - 1}} + {x^k}\left( 1 \right)$ $\frac{d}{{dx}}{x^{k + 1}} = k{x^{k - 1 + 1}} + {x^k}$ $\frac{d}{{dx}}{x^{k + 1}} = k{x^k} + {x^k}$ $\frac{d}{{dx}}{x^{k + 1}} = {x^k}\left( {k + 1} \right)$ = RHS
∴ p(n) is true for x = k+1
∴ PMI. $\frac{d}{{dx}}{x^n} = n{x^{n - 1}} \qquad \text{true for all n ∈N}$

Question (20)

Using the fact that sin(A+B) = sinAcosB + cosAsinB and the differentiation obtain the sum formula for cosines

Solution

Differentiating w.r.t. x $\cos \left( {A + B} \right)\frac{d}{{dx}}\left( {A + B} \right) = \sin A\frac{d}{{dx}}\cos B + \cos B\frac{d}{{dx}}\sin A + \cos A\frac{d}{{dx}}\sin B + \sin B\frac{d}{{dx}}\cos A$ $\cos \left( {A + B} \right)\left( {\frac{{dA}}{{dx}} + \frac{{dB}}{{dx}}} \right) = \sin A\left( { - \sin B} \right)\frac{{dB}}{{dx}} + \cos B\cos A\frac{{dA}}{{dx}} + \cos A\cos B\frac{{dB}}{{dx}} + \sin B\left( { - \sin A} \right)\frac{{dA}}{{dx}}$ $\cos \left( {A + B} \right)\frac{d}{{dx}}\left( {A + B} \right) = \left( {\cos A\cos B - \sin A\sin B} \right)\frac{{dB}}{{dx}} + \left( {\cos A\cos B - \sin A\sin B} \right)\frac{{dA}}{{dx}}$ $\cos \left( {A + B} \right)\left( {\frac{{dA}}{{dx}} + \frac{{dB}}{{dx}}} \right) = \left( {\cos A\cos B - \sin A\sin B} \right)\left( {\frac{{dA}}{{dx}} + \frac{{dB}}{{dx}}} \right)$ $\cos \left( {A + B} \right) = \cos A\cos B - \sin A\sin B$

Question (21)

Does there exist a function which is continuous everywhere but not differentiatiable at exactly two points? Justify your answer.

Solution

Yes it exists that function is continuous at every value of x, but not differentiable at two points
To justfy we will consider function f as follows.
f(x) = |x| - |x + 1| $\begin{array}{l}if\;x \le - 1,\\|x + 1| = - (x + 1),|x| = - x\end{array}$ $f(x) = - x - [ - (x + 1)] = 1$ $\begin{array}{l}if\; - 1 < x \le 0,\\|x + 1| = x + 1,|x| = - x\end{array}$ $f(x) = - x - (x + 1) = - 2x - 1$ $\begin{array}{l}if\;x > 0,\\|x| = x,|x + 1| = x + 1\end{array}$ $f(x) = x - (x + 1) = - 1$ $So\;\;f(x) = 1\;\;if\;x \le - 1$ $= - 2x - 1\;if\; - 1 < x \le 0$ $= - 1\;if\;x > 0$ The function is break at x = -1, and x = 0.so check the continuity at x = -1 and at x = 0. For the other value of x it is continuous.
Let us check at x = -1, f(-1) = -2(-1)-1 = 2 - 1 = 1
$LHL = \mathop {\lim }\limits_{x \to - {1^ - }} f(x) = \mathop {\lim }\limits_{x \to - {1^ - }} 1 = 1$ $RHL = \mathop {\lim }\limits_{x \to - {1^ + }} f(x) = \mathop {\lim }\limits_{x \to - {1^ + }} - 2x - 1 = - 2( - 1) - 1 = 1$ $\mathop {\lim }\limits_{x \to - {1^ - }} f(x) = f( - 1) = \mathop {\lim }\limits_{x \to - {1^ + }} f(x)$ So f(x) is continuous at x = -1.
Let us check at x = 0, f(0) = -2(0) - 1 = 0 - 1 = - 1.
$LHL = \mathop {\lim }\limits_{x \to {0^ - }} f(x) = \mathop {\lim }\limits_{x \to - {0^ + }} - 2x - 1 = - 2(0) - 1 = - 1$ $RHL = \mathop {\lim }\limits_{x \to {0^ + }} f(x) = \mathop {\lim }\limits_{x \to - {0^ + }} - 1 = -1$ $\mathop {\lim }\limits_{x \to - {0^ - }} f(x) = f(0) = \mathop {\lim }\limits_{x \to - {0^ + }} f(x)$ So f(x) is continuous at x = 0.
So f(x) is continuous at every point of x. Let us check the differeniability at x = - 1
f(-1) = 1
$lhl = \mathop {\lim }\limits_{x \to - {1^ - }} \frac{{f(x) - f( - 1)}}{{x - ( - 1)}} = \mathop {\lim }\limits_{x \to - {1^ - }} \frac{{1 - 1}}{{x + 1}} = 0$ $Rhl = \mathop {\lim }\limits_{x \to - {1^ + }} \frac{{f(x) - f( - 1)}}{{x - ( - 1)}} = \mathop {\lim }\limits_{x \to - {1^ + }} \frac{{ - 2x - 1 - 1}}{{x + 1}} = \mathop {\lim }\limits_{x \to - {1^ + }} \frac{{ - 2(x + 1)}}{{x + 1}} = - 2$ $\mathop {\lim }\limits_{x \to - {1^ - }} \frac{{f(x) - f( - 1)}}{{x - ( - 1)}} \ne \mathop {\lim }\limits_{x \to - {1^ + }} \frac{{f(x) - f( - 1)}}{{x - ( - 1)}}$ so f is not differentiable at x= - 1.
To check at x = 0
f(0) = -2(0) - 1 = -1.
$\mathop {\lim }\limits_{x \to {0^ - }} \frac{{f(x) - f(0)}}{{x - (0)}} = \mathop {\lim }\limits_{x \to {0^ - }} \frac{{ - 2x - 1 - ( - 1)}}{x} = \mathop {\lim }\limits_{x \to {0^ - }} \frac{{ - 2(x)}}{x} = - 2$ $\mathop {\lim }\limits_{x \to {0^ + }} \frac{{f(x) - f(0)}}{{x - (0)}} = \mathop {\lim }\limits_{x \to {0^ + }} \frac{{ - 1 - ( - 1)}}{x} = \mathop {\lim }\limits_{x \to {0^ + }} \frac{0}{x} = 0$ $\mathop {\lim }\limits_{x \to {0^ - }} \frac{{f(x) - f(0)}}{{x - (0)}} \ne \mathop {\lim }\limits_{x \to {0^ + }} \frac{{f(x) - f(0)}}{{x - (0)}}$ Hence f(x) is also not differentiable at x = 0.
Hence the function was continuous at every point but not differentiable at two points.

Question (22)

$\text{If}\qquad y = \left| {\begin{array}{*{20}{c}}{f\left( x \right)}&{g\left( x \right)}&{h\left( x \right)}\\l&m&n\\a&b&c\end{array}} \right|$ Prove that $\frac{{dy}}{{dx}} = \left| {\begin{array}{*{20}{c}}{f'\left( x \right)}&{g'\left( x \right)}&{h'\left( x \right)}\\l&m&n\\a& b&c\end{array}} \right|$

Solution

$\text{If}\qquad y = \left| {\begin{array}{*{20}{c}}{f\left( x \right)}&{g\left( x \right)}&{h\left( x \right)}\\l&m&n\\a&b&c\end{array}} \right|$ Expanding this matrics along first row we get,
y=f(x)[mc - bn] - g(x) [ lc - an ] + h(x) [ lb - ma]
Diff. w.r. t. x, we get ,
dy / dx = (mc - bn)f'(x) - ( lc - an)g'(x) + ( lb - ma) h'(x)
it can be rearrange in the matrix as
$\frac{{dy}}{{dx}} = \left| {\begin{array}{*{20}{c}}{f'\left( x \right)}&{g'\left( x \right)}&{h'\left( x \right)}\\l&m&n\\a& b&c\end{array}} \right|$

Question (23)

If y = eacos-1x , -1 ≤ x ≤ 1, show that $\left( {1 - {x^2}} \right)\frac{{{d^2}y}}{{d{x^2}}} - x\frac{{dy}}{{dx}} - {a^2}y = 0$

Solution

Differentiating w.r.t. x $\frac{{dy}}{{dx}} = {e^{a{{\cos }^{ - 1}}x}}\frac{d}{{dx}}\left( {a{{\cos }^{ - 1}}x} \right)$ ${y_1} = {e^{a{{\cos }^{ - 1}}x}}\frac{{ - a}}{{\sqrt {1 - {x^2}} }}$ $\sqrt {1 - {x^2}} {y_1} = - a{e^{a{{\cos }^{ - 1}}x}}$ Differentiating w.r.t. x again $\sqrt {1 - {x^2}} \frac{{d{y_1}}}{{dx}} + {y_1}\frac{d}{{dx}}\sqrt {1 - {x^2}} = - a{e^{a{{\cos }^{ - 1}}x}} \cdot \frac{d}{{dx}}\left( {a{{\cos }^{ - 1}}x} \right)$ $\sqrt {1 - {x^2}} {y_2} + {y_1}\left( {\frac{{ - 2x}}{{2\sqrt {1 - {x^2}} }}} \right) = - a{e^{a{{\cos }^{ - 1}}x}} \cdot \frac{{ - a}}{{\sqrt {1 - {x^2}} }}$ $\sqrt {1 - {x^2}} {y_2} - \frac{{x{y_1}}}{{\sqrt {1 - {x^2}} }} = \frac{{{a^2}{e^{a{{\cos }^{ - 1}}x}}}}{{\sqrt {1 - {x^2}} }}$ (1-x2)y2 - xy1 = a2y $\left( {1 - {x^2}} \right)\frac{{{d^2}y}}{{d{x^2}}} - x\frac{{dy}}{{dx}} - {a^2}y = 0$